Avaliação institucional externa: uma análise da literatura científica e da legislação acerca da faculdade isolada - Machado, Rosa Maria da Rocha Neves (2020)
This study seeks to reflect on the dynamics of Educational Laws and Norms imposed on administrative and academic management in Higher Education Institutions (HEIs), especially with regard to autonomy and the importance of obtaining good grades in institutional evaluation procedures. The theme reveals contradictions and undefinitions, which generated the question: assuming that the institutional evaluation, guided by the perspectives of the National Higher Education Evaluation System (Sinaes), is parameterized to the Universities, to what extent the Isolated Colleges (IC), said as non-university, to which the same assessment applies, do they have their institutional identity considered in the institutional evaluation process, giving them conditions for their emancipation? The objectives were to understand the application of the external institutional evaluation instrument, issued by the Anísio Teixeira National Institute of Educational Studies and Research (Inep) in the isolated colleges (IC), as well as to present an intervention proposal for the daily life of the Institutional Prosecutor, subject, in HEIs of Brazil, responsible for the interface with the Ministry of Education (MEC). For the organization of this study, were initially explored historical aspects that circumvent the implementation of universities in Brazil, bringing the contribution of the Faculties over time. In an expanded analysis of the contours of an IC, factors such as diversity, interrelationships and adaptation mechanisms to comply with legal aspects and their social responsibility are explored. In addition, are described the constituents of the External Institutional Evaluation, as defined by Sinaes - its criteria and their adequacy to the institutional reality. The methodology was organized, on the one hand, by carrying out a bibliographic survey, by analyzing research related to the theme, then highlighting normative documentation studies, and, on the other hand, by systematic observation and exploratory study that took place in an IC. This study meets the requirements of a Professional Master's Degree in Training of Educational Managers and presents, during the Methodology, the exploratory study, which represents an intervention proposal articulated to the demands of an IC, aiming at the improvement of the formative work, from the perspective of the maintainer and the educational manager. It was concluded that the expectations of the external evaluation proposed by Sinaes (Inep) when using the grade of the National Student Performance Examination (Enade) as a factor of automatic renewal of authorizing acts, is based on subjective characteristics, presenting contradictions, as far as where HEIs are no longer subject to the other criteria of the evaluation instruments axes. Concerning the emancipation of the isolated faculties, it was possible to verify that there is in the proposed educational legislation changes in relation to the autonomy of non-university HEIs, linked to evaluative questions and excellent results achieved by them, which will allow these HEIs to issue diplomas, increased supply of vacancies, implementation of undergraduate courses and other processes that would be resolved quickly and simplified, without the need for prior authorization by MEC. Within the scenario of higher education with quality, we face the challenges of institutional management, explaining the pursuit of excellence, according to the institutional organization of HEI and academic prerogatives, which can claim the expansion and increase of quality in a perspective that it does not aim to achieve the accreditation of a University Center, not even the status of a University, but to fulfill a mission of being a center of excellence in management and training of professionals and increasing competitiveness of Brazilian organizations, considering that Private HEIs are understood as companies within the scope of the world economy.